Implementasi Kebijakan Penyelenggaraan Kewaspadaan Dini di Daerah Provinsi Kalimantan Utara - Frans Johannes Lambok Lumban Tobing; Dandan Haryono; Agus Priyanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to describe and analyze the implementation of early warning system policies in the regions under the Kesbangpol (National Unity and Politics Agency) of North Kalimantan Province and identify factors that support and hinder the implementation of these policies in the region. The research method used is a phenomenological case study model. The results indicate that the implementation of early warning system policies in North Kalimantan Province has not been fully successful, given the increase in types of crimes and criminal activities over the past two years. Additionally, there are still several district governments that have not yet established FKDM (Early Warning Community Forum) as required by this policy, as stipulated in the Ministry of Home Affairs Regulation No. 46 of 2019 concerning Early Warning Systems. Supporting factors for the implementation of early warning system policies in North Kalimantan Province include: (a) the standards and targets of the early warning system policy have been well implemented; (b) inter-organizational relationships indicate good communication and coordination among all stakeholders; (c) the characteristics of policy implementers are good, with the primary implementer being the Kesbangpol agency, which is organizationally suitable for implementing early warning policies; (d) the social, political, and economic conditions are conducive, and political elite support is very good; (e) the disposition/attitudes of policy implementers show a strong understanding of the content and objectives of the early warning policy. On the other hand, the factors hindering implementation include: the number and competence of human resources, as well as inadequate budgetary resources and facilities.